Manajemen Organisasi Pendidikan Anak Usia Dini: Studi Kasus di TK IT Insan Madani - Arneta Widia; Anugrah Satria Dermawan; Raihan Nazrey Suseno; Inayatu Safitri; Zuhrona Siregar (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2025)
This study aims to describe and analyze the implementation of organizational management at TK IT Insan Madani, an Islamic-based early childhood education institution. The focus of the research includes organizational structure, task division, communication patterns, and the leadership style applied. This study employs a descriptive qualitative approach using observation, in-depth interviews, and documentation as data collection techniques. The findings indicate that organizational management at TK IT Insan Madani is effectively implemented. The organizational structure is well-organized, duties and responsibilities are clearly distributed, communication flows in an open and two-way manner, and the head of the school adopts a transformational and participatory leadership style. These findings suggest that good organizational management has a positive impact on improving the quality of early childhood education services. The implications of this research are expected to serve as a managerial model for other PAUD institutions, particularly those with private or religious-based backgrounds.